Detection and quantitation of tetanus antitoxin in blood donations. - Barr, A (1975)
Passive haemagglutination and IEOP have been used both to detect and to measure tetanus antitoxin in human donor sera. Forty percent of blood donors had detectable antitoxin but only 9% had levels suitable for production of human antitetanus immuoglobulin (larger than or equal to 2 IU/ml). The incidence of high titre antitoxin was significantly greater in men and was unrelated to the ABO blood group system. The prevalence of antitoxin in selected donor groups and immunized staff is shown.